Penerapan Forecasting Untuk Penentuan Target Penjualan Pada Cv. Mekar Jaya Sentosa Dengan Metode Least Square - Kamal, Bahri; Rahmadiane, Ghea Dwi (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
Changes in the current era are very fast and fast, especially changes in the industrial sector which are increasingly diverse and are required to create innovations so that they can have competitiveness in each of these producers or industry players. The company always makes a work plan to determine sales targets to be achieved in the future, one of which is a distributor company. Determining sales targets means that the company tries to predict future sales by taking into account future conditions and past conditions. However, so far the determination of future targets is not objective because it is only based on management intuition. The purpose of this study is to develop a form of forecasting application on CV. Mekar Jaya Sentosa utilizing the Least Square Method as a means of calculating the volume of sales in the coming period. The location that will be used as this research is in CV. Mekar Jaya Sentosa, Kramat District, Tegal Regency, Indonesia. The study's data were taken straight from informants in the form of sales data and interview data regarding the procedure for determining sales targets CV. Mekar Jaya Sentosa. This study's analytical approach makes use of descriptive analysis. According to the study's findings, it can be projected that sales for the next period, namely July 2023, will be 225,252.96 units or can be rounded up to 225,253 units of Aqua products. Based on the research of (Walangadi & Surya Kumala, 2019) and (Rahmadiane, 2022b) that setting targets can use combining qualitative and quantitative approaches. The numerical approach is seen from the outcomes of forecasting least squares calculations, while the qualitative method a seen from the consideration of the opinions of stakeholders within the company, for example the marketing department, supervisors, depot heads, and consumers.